Analysis of the influence of internal control and competence of village apparatuses on village fund management fraud - Rudi Ginting; Suhendar Suhendar; Wildoms Sahusilawane; Mekar Meilisa Amalia; Rahmat Jatnika (Enrichment : Journal of Management, 2022)
This research is motivated by the importance of preventing fraud in village fund management. This study aims to analyze the effect of internal control and competence of village apparatus on village fund management fraud. This research method is a descriptive method with a quantitative approach. The population in this study is all village apparatus in Indonesia. The sample for this research was 100 village officials who were taken by purposive sampling. The data source used in this study is primary data from the results of distributing questionnaires via Google form to the village heads who are the sample. The collected data was processed and analyzed with the help of Excel and SPSS version 24. The results of this study indicate that 1) internal control partially has a positive and significant effect on fraud in the management of village funds, 2) competence of village apparatus partially has a positive and significant effect on fraud in the management of funds village, and 3) internal control and competence of village apparatus simultaneously have a positive and significant effect on village fund management fraud. These findings imply that if the village government wants to prevent fraud in managing village funds, then the village government must improve internal control and the competence of village apparatus.